The Traditional Role of CRM and Social Media Marketing in Increasing Customer Loyalty Mediated by Commitment, Trust, and Purchase Satisfaction: Online Cosmetics and Skincare - Boyke Boyke; Kurniawati Kurniawati; Yolanda Masnita (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study was conducted with the aim of examining the effect of Traditional CRM and Social Media Marketing on Customer Loyalty both directly and indirectly through Commitment, Satisfaction and Trust. The type of research used is hypothesis testing by taking samples using purposive sampling, namely respondents who have worked and made purchases of cosmeceuticals and skin care with the number of samples collected as many as 221. The analytical tool used is SEM-PLS. The findings show Traditional CRM is proven to have a positive effect on Customer Loyalty directly while Social Media Marketing is not proven to have a direct effect on Customer Loyalty. Commitment is proven to mediate the positive influence of Traditional CRM and Social Media Marketing on Customer Loyalty.  Satisfaction is not proven to mediate the positive effect of Traditional CRM and Social Media Marketing on Customer Loyalty. Trust is proven to mediate the positive effect of Traditional CSM and Social Media Marketing on Customer Loyalty.